Genetic transformation of black pepper (piper nigrum L) for phytophthora foot rot resistance/tolerance - Lissamma Joseph (Department of Plantation Crops and Spices, College of Horticulture, 2007)
Investigations on "Genetic transformation of black pepper (Piper nigrum L.) for Phytophthora foot rot resistance/tolerance" were carried out at the Department of Plantation Crops and Spices, and Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during 2001-2006. Three selected black pepper varieties Panniyur 1, 4 and 6 were utilized for the study.